Non-vascular interventional radiology in the paediatric alimentary tract. Issue 112 (March 2019) - Patel, Premal A.; Minhas, Kishore; Ang, Jestine; Stuart, Sam; De Coppi, Paolo; Gnannt, Ralph
Highlights: Paediatric interventional radiology offer minimally invasive treatments. IR treatment in the GI tract is a safe and effective alternative to more invasive procedures. Sclerotherapy, stricture management, stenting, and enteral access are discussed. Abstract: Paediatric interventional radiology is an evolving speciality which is able to offer numerous minimally invasive treatments for gastrointestinal tract pathologies. Here we describe interventions performed by paediatric interventional radiologists on the alimentary tract from the mouth to the rectum. The interventions include sclerotherapy, stricture management by dilation, stenting and adjunctive therapies such as Mitomycin C administration and enteral access for feeding, motility assessment and administration of enemas.